Incidental Pancreatic Cystic Lesions: Is There a Relationship with the Development of Pancreatic Adenocarcinoma and All-Cause Mortality? - Chernyak, Victoria (Radiology, 2015)
PURPOSE: To establish the effect of incidental pancreatic cysts found by using computed tomographic (CT) and magnetic resonance (MR) imaging on the incidence of pancreatic ductal adenocarcinoma and overall mortality in patients from an inner-city urban U.S. tertiary care medical center. MATERIALS AND METHODS: Institutional review board granted approval for the study and waived the informed consent requirement. The study population comprised cyst and no-cyst cohorts drawn from all adults who underwent abdominal CT and/or MR November 1, 2001, to November 1, 2011. Cyst cohort included patients whose CT or MR imaging showed incidental pancreatic cysts; no-cyst cohort was three-to-one frequency matched by age decade, imaging modality, and year of initial study from the pool without reported incidental pancreatic cysts. Patients with pancreatic cancer diagnosed within 5 years before initial CT or MR were excluded. Demographics, study location (outpatient, inpatient, or emergency department), dates of pancreatic adenocarcinoma and death, and modified Charlson scores within 3 months before initial CT or MR examination were extracted from the hospital database. Cox hazard models were constructed; incident pancreatic adenocarcinoma and mortality were outcome events. Adenocarcinomas diagnosed 6 months or longer after initial CT or MR examination were considered incident. RESULTS: There were 2034 patients in cyst cohort (1326 women [65.2%]) and 6018 in no-cyst cohort (3,563 [59.2%] women); respective mean ages were 69.9 years ± 15.1(standard deviation) and 69.3 years ± 15.2, respectively (P = .129). The relationship between mortality and incidental pancreatic cysts varied by age: hazard ratios were 1.40 (95% confidence interval [CI]: 1.13, 1.73) for patients younger than 65 years and 0.97 (95% CI: 0.88, 1.07), adjusted for sex, race, imaging modality, study location, and modified Charlson scores. Incidental pancreatic cysts had a hazard ratio of 3.0 (95% CI: 1.32, 6.89) for adenocarcinoma, adjusted for age, sex, and race. CONCLUSION: Incidental pancreatic cysts found by using CT or MR imaging are associated with increased mortality for patients younger than 65 years and an overall increased risk of pancreatic adenocarcinoma. © RSNA, 2014